O desenvolvimento do cantor lírico numa abordagem de base psicanalítica: reflexões sobre uma proposta de trabalho - Flaborea, Camila (2007)
My intention in writing this paper is to reflect about a proposal of work with lyric singers that attaches the artistic development to the personal development. The presented approach has a psychoanalytic basis, especially founded on the English Middle Group. The theoretical references, besides Freud, are Michael Balint and Hans Loewald. Together with the psychoanalysis method base, body therapy techniques (Calatonia and Subtle Touches ) are used, as well as dance techniques (Klauss Vianna method) and drama techniques. A clinical diary, constructed for the three presented cases, was analysed so it became possible to figure out the transference handling within a non psychoanalytical context. I could notice that the object relations and the sublimation are aspects deeply linked to the artistic construction of the scene. Due to this perception, my intention is to discuss such processes both in psychoanalytic and artistic settings. To conclude, I have made an inventory of wins, losses, borders and possibilities that have brought about through this approach. In final considerations, I will present the professional changes occurred on my professional posture due to this experience